The Relationship between Patient Knowledge and Anxiety on MRI Examination at Dr. M Djamil Hospital - Santa Mareta; Oktavia Puspita Sari; Yori Rahmadianti; Alfandi Alfandi (Oshada, 2025)
A person's knowledge affects anxiety, if a person has too much information or conflicting knowledge it can confuse and make a person feel unsure, which can increase anxiety. This research method uses quantitative correlation analytic method with cross sectional design. This research was conducted at Dr. M Djamil Padang Hospital. The population of this study is the total population of patient visit data from May to July 2023 with a total of 843. The sample of this study used nonprobability sampling technique with accidenta sampling method which amounted to 89 respondents using the slovin formula. data collection was carried out by questionnaire, the data obtained was then processed using the SPSS application with the sperman rank correlation test. The results show that in this study there is one characteristic, namely the relationship between the level of knowledge and the level of anxiety which shows Ho is rejected and Ha is accepted, it can be concluded that there is a significant relationship between the patient's level of knowledge about MRI examination with the level of anxiety on MRI in the Radiology installation of Dr. M Djamil Padang Hospital.